2022
DOI: 10.1007/s13178-022-00702-1
|View full text |Cite
|
Sign up to set email alerts
|

Vulnerability Conditions in a Cohort of Men Who Have Sex with Men Who Engage in Chemsex in Barcelona City: a Cross-Sectional Study

Abstract: Introduction Chemsex is a dynamic phenomenon with cultural variation. There is limited information about its prevalence and specific characteristics in our geographical area. Methods In this cross-sectional study of a series of gay, bisexual, and other men who have sex with men (gbMSM) who engaged in chemsex and were attending the Hospital Clinic of Barcelona, Spain, between March 2018 and May 2019, we aimed to identify potential vulnerabilities and descri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 42 publications
(48 reference statements)
1
4
0
1
Order By: Relevance
“…Chemsex has an impact on sexual health and increases the risk of transmission of HIV, hepatitis C virus (HCV), and other sexually transmitted diseases (STDs) [12]. Data from our hospital corroborate the aforementioned concerns and describe a heterogeneous cohort of chemsex users with health, social, and psychological implications [13].…”
Section: Introductionsupporting
confidence: 61%
“…Chemsex has an impact on sexual health and increases the risk of transmission of HIV, hepatitis C virus (HCV), and other sexually transmitted diseases (STDs) [12]. Data from our hospital corroborate the aforementioned concerns and describe a heterogeneous cohort of chemsex users with health, social, and psychological implications [13].…”
Section: Introductionsupporting
confidence: 61%
“…The recent increase in people who engage in chemsex in several cities in Europe [ 24 26 , 42 ], including in Barcelona [ 27 30 ], may have influenced our users’ elevated substance consumption data. The chemsex rate in our cohort was higher than that described in other international studies, as we found that 87% of people who used drugs engaged in chemsex ( n / N = 160/292, 55% of the whole cohort), compared to 38.5% detected in a multicenter English study [ 31 ] or 42.6% in a Paris cohort [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…These practices also confer a higher risk for bacterial STIs [ 23 ]. The chemsex phenomenon is rapidly spreading in European countries [ 24 26 ], and Barcelona is the Spanish city with the highest prevalence [ 27 30 ]. PrEP could be offered as an additional HIV and STI prevention strategy to people who engage in chemsex as part of a comprehensive risk reduction program [ 31 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…An uncontrolled HIV VL has been identified as another risk factor for CA-MRSA infections and recurrence [ 14 , 15 ]. We have previously reported that people who engage in chemsex have significantly higher HIV viral load than general PLWH from our cohort [ 8 ], as one of the potential consequences of problematic chemsex practice.…”
Section: Discussionmentioning
confidence: 99%
“…This is an ambispective longitudinal study carried out between February 2018 and January 2022 in the Hospital Clinic of Barcelona (HCB), Spain. HCB follows a prospective cohort of 299 PLWH who engage in chemsex, as a result of a pilot study [ 8 ] within the global cohort of nearly 6000 PLWH. The present study was developed within this prospective cohort.…”
Section: Methodsmentioning
confidence: 99%